Influence of Social Capital on Small and Medium Enterprises Performance in Wakiso District, Uganda. - Mbowa, Henry Stanley; Businge, Mbabazi Phelix; Ssemaluulu, Paul; Eton, Marus (Kabale University, 2023)
Purpose: This study examined the influence of Social Capital (SC) on the performance of Small and Medium Enterprises (SMEs) in Wakiso District. Specifically, we identified forms of SC and assessed how they influenced SMEs’ performance in Kitemu Ward. Research methodology: Using qualitative and quantitative methodologies, the study solicited data from 40 participants through interviews and a self-administered questionnaire. Data were edited, cleaned, coded, and entered into MS Excel to generate frequencies and graphs. Content value analysis was used to transcribe the qualitative data and group them into subthemes. Results: The results revealed internal forms of SC, such as friends/peers, trustworthiness, personal saving, family, and social links, while external forms of SC were customers, financial institutions, governments, and companies. Further, SC influences the customer base, leads to high profits, increases sales volume, and enhances creativity and innovation. Limitations: Financial constraints prevented researchers from eliciting data throughout the study area. Furthermore, the small sample size might limit the generalization of the study results to the entire district. In addition, time and data collection biases have implications for this study. Contribution: This study is vital because there are no studies carried out in Kitemu Ward on SC and its influence on SMEs’ performance. The findings can be used by policy and decision-makers to design mechanisms for SMEs’ proprietors to integrate SC into business operations. The literature reveals that SC forms enhance sales, profits, market share, customer base, and accessibility to finance. Novelty: This original study was conducted primarily among women proprietors and managers of SMEs because they are reliable and provide firsthand information as compared to men. Thus, if adopted, the findings are vital for other business proprietors and managers to improve business performance.